Needs Analysis of AI-Integrated Game-Based Multimedia for Programming Algorithm Material - Ranita Sari; Makmum Raharjo; Farhan Yadi (Postgraduate, University of Mataram, 2026)
Learning Programming Algorithms, which are abstract, logical, and sequential in nature, often pose challenges for students in understanding concepts optimally. In addition, the use of learning media that does not align with students’ needs becomes an essential factor affecting the success of the learning process. This study aims to analyze the needs for developing gamified multimedia integrated with an AI Chatbot in Programming Algorithm materials that are relevant to students’ learning needs. The research method employs a quantitative descriptive approach through questionnaires distributed to 11th-grade students and teachers at SMAN 1 Sembawa, SMAN 2 Sembawa, SMAN 1 Banyuasin III, and SMAN 2 Plus Banyuasin III. Data analysis was conducted by calculating the percentage of needs based on four aspects: students, teachers, learning media, and instructional design. The results show that the needs of students, teachers, learning media, and instructional design fall into a high category, with percentages of student needs (85.78%), teacher needs (91.85%), learning media needs (89.23%), and instructional needs (80.52%). These findings emphasize the necessity of developing interactive and adaptive learning media. Overall, the development of gamified multimedia integrated with an AI Chatbot is considered an appropriate alternative to address these needs, as it can provide instant feedback through the AI chatbot and enhance student engagement through gamification. This media is expected to help students understand abstract concepts in Programming Algorithms, increase motivation and engagement, and promote more meaningful learning.